2014
DOI: 10.1242/jeb.104455
|View full text |Cite
|
Sign up to set email alerts
|

Thermal limitation of performance and biogeography in a free-ranging ectotherm: insights from accelerometry

Abstract: Theoretical and laboratory studies generally show that ectotherm performance increases with temperature to an optimum, and subsequently declines. Several physiological mechanisms probably shape thermal performance curves, but responses of free-ranging animals to temperature variation will represent a compromise between these mechanisms and ecological constraints. Thermal performance data from wild animals balancing physiology and ecology are rare, and this represents a hindrance for predicting population impac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
22
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 44 publications
(76 reference statements)
3
22
1
Order By: Relevance
“…Recently, ODBA has also been shown to vary strongly with temperature in wild fishes and in a manner consistent with theoretical expectations (Angilletta, 2009) of thermal performance curves (Gannon et al, 2014;Payne et al, 2016). Recently, ODBA has also been shown to vary strongly with temperature in wild fishes and in a manner consistent with theoretical expectations (Angilletta, 2009) of thermal performance curves (Gannon et al, 2014;Payne et al, 2016).…”
Section: Standardization Of Catch Datasupporting
confidence: 61%
See 1 more Smart Citation
“…Recently, ODBA has also been shown to vary strongly with temperature in wild fishes and in a manner consistent with theoretical expectations (Angilletta, 2009) of thermal performance curves (Gannon et al, 2014;Payne et al, 2016). Recently, ODBA has also been shown to vary strongly with temperature in wild fishes and in a manner consistent with theoretical expectations (Angilletta, 2009) of thermal performance curves (Gannon et al, 2014;Payne et al, 2016).…”
Section: Standardization Of Catch Datasupporting
confidence: 61%
“…Dicken et al, 2016;Holmes et al, 2012). For example, accelerometers quantify mechanical work done by animals (Gleiss, Wilson, & Shepard, 2011;Wilson et al, 2006), and have shown promise as a tool for measuring temperature's influence on locomotor performance in several wild estuarine fish species (Gannon et al, 2014;Payne et al, 2016). Approaches that additionally account for temperature's influence on performance of sharks should be more powerful and potentially more robust than those based solely on correlative distribution data (Davis et al, 1998;.…”
mentioning
confidence: 99%
“…Of the few studies published on the relationship between activity levels and temperature, most are qualitative (e.g. Tomlinson and Phillips 2012); only rarely do papers present quantified relationships between voluntary activity and temperature (see also Biro et al 2010;Gannon et al 2014;Halcrow and Boyd 1967;Latimer et al 2011;Lighton and Duncan 2002;Morgan 1984Morgan , 1987Van Donk and De Wilde 1981). While several papers have included activity measures in MR-temperature experiments, these studies have typically been interested only in the presence or absence of activity, focussing on the time-point that activity ceases during temperature ramping protocols (Folk et al 2007;Lighton 2007;Lighton and Turner 2004;Stevens et al 2010).…”
mentioning
confidence: 99%
“…Technological advancements are illustrated by the change of methods used to study movement ecology (Table 4), with the use of acoustic telemetry doubling between SDU and the Sharks International conferences, and the sole use of conventional identification tags declining from 2.7% to 0.4%. Acoustic telemetry has continued to evolve, with new tags providing additional information, such as changes in the pH of the stomach contents of the tagged individual, which can reflect feeding events (Papastamatiou et al 2007), or an acceleration vector that reflects activity level, which is used to infer physiological processes influencing movements (Gannon et al 2014). The benefits of using acoustic telemetry are accentuated by global monitoring networks, such as the Australian Animal Tagging and Monitoring System (AATAMS) and the international equivalent, the Ocean Tracking Network (OTN) (O'Dor et al 2008), which have led to an increase in acoustic coverage and the ability to gather movement data over much larger spatial scales than independent studies can cover.…”
Section: Topics and Methodsmentioning
confidence: 99%